(untitled) (Psychology Travelogs, 2023)
The article examines the impact of middle school students’ anxiety on educational activities in wartime conditions. The importance of studying this issue is substantiated and it is stated that in connection with the pandemic and the war in Ukraine, significant changes have taken place in the life of every person, including in the life of students, namely the introduction of distance education. The views of scientists regarding the study of the concept of "anxiety", "school anxiety" are considered. It was determined that anxiety is a fairly stable individual characteristic of a person, which reflects his tendency to restlessness and implies that he has a tendency to perceive quite a lot of situations as threatening, responding to each of them with a certain reaction. The results of Ukrainian research on the impact of anxiety among middle school students on educational activities were analyzed and the factors causing anxiety were determined. The leading factors of the emergence of school anxiety are the peculiarities of the child’s nervous system, the style of upbringing, the interaction of parents with each other, excessive demands on the personality of the teenager, and in some cases, unfair behavior of the teacher. Other factors include: fear of mistakes, students’ answers in front of the class, criticism of the teacher and peers, unsatisfactory evaluation, condemnation from parents, teachers. The psychological characteristics of adolescents are described, and the relationship between adolescence and the occurrence of anxiety is also considered. The results of an empirical study of the impact of middle school students’ anxiety on educational activities in war conditions are highlighted. It was determined that the majority of students have a high level of situational anxiety, which negatively affects the success of educational activities, because children are motivated to learn, have a need for knowledge, but today’s conditions significantly hinder the acquisition of truly quality education. We see prospects for further research in providing practical recommendations to middle school students to reduce the level of anxiety in war conditions.